Higher spatial than seasonal beta diversity of soil protists along elevation gradients - Bruni, Estelle Patricia; Juan Lorite; Julio Peñas; Mulot, Matthieu; Pascal Vittoz; Fournier, Bertrand; Mitchell, Edward; Lentendu, Guillaume (My University, 2024)
Biodiversity patterns along elevation gradients have long been studied for plants and animals, but only quite recently for soil microorganisms, especially protists (eukaryotes excluding plants, animals, and fungi). Microorganisms have shorter generation times than macroorganisms, and their abundance, diversity, and community structure are known to vary rapidly in response to abiotic and biotic factors. If microbial diversity varies more seasonally than spatially, a single sampling campaign along an elevation gradient, with contrasted phenologies, could introduce bias into biodiversity studies comparing multiple elevation gradients across different seasons, habitats, regions or latitudes. To address this question, we investigated the relative magnitude of spatial versus temporal diversity (alpha diversity) and community turnover (beta diversity) of soil protist communities along elevation gradients in two distant European mountain ranges. We collected soil samples in forests and grasslands below the treeline along five elevation gradients in two consecutive seasons (spring and summer) in the Spanish Sierra Nevada and the Swiss Alps, covering two distinct biogeographic regions. Using general eukaryotic primers and amplicon sequencing of soil environmental DNA, we decomposed total protist amplicon sequence variants diversity into local alpha- and beta diversity components and identified climatic and edaphic predictors of biodiversity patterns using redundancy analyses. Soil protist communities varied spatially within and among transects but temporal turnover was comparatively low. The best edaphic predictors of community variations were the same in spring and summer, but their explanatory power differed among seasons. The dominant spatial component of beta diversity suggests that patterns of soil protist communities along elevation gradients are more strongly driven by spatial heterogeneity than inter-seasonal turnover. Thus, in temperate climates, our results suggest that sampling only once between the end of spring and late summer across an elevation gradient does not introduce bias due to phenological differences when comparing beta diversity across multiple gradients. Spatio-temporal dynamics of soil protists communities were studied in forests and grasslands below the tree line along five elevation gradients in the Spanish Sierra Nevada and the Swiss Alps during two consecutive seasons (spring and summer). The total diversity of soil protist communities was predominantly shaped by beta-diversity components with spatial heterogeneity rather than temporal turnover as the main driver of soil protist community composition. Community dissimilarity of soil protists did not differ in response to temporal changes between habitats (i.e., forests versus grasslands) The significant edaphic predictors of protist community composition were highly similar in the Swiss Alps and identical in the Spanish Sierra Nevada between both seasons, but their explanatory power varied between spring and summer. Soil protist beta diversity patterns along different elevation gradients remained constant between seasons. This suggests that, in temperate climates, sampling at one time across an elevation gradient will not bias results stemming from phenological contrasts, allowing comparison of beta diversity patterns along such gradients between regions even if sampling is not simultaneous.